The Effect of Functıonal Traınıng and Narrow Area Traınıng Applıed to U14-U15 Category Football Players on Selected Blood Parameters - Ibrahim Kubilay Türkay, Gürhan Suna, Melisa Cansu Uzun (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to examine the effects of 8-week functional training and narrow field studies on selected blood parameters of U14-U15 football players. Method: A total of 22 football players in the U14-U15 category participated in the study. In the study, functional training and narrow space exercises were performed 3 days a week for 8 weeks in the experimental group, and technical training was performed on the control group 3 days a week for 8 weeks. A "Family Informed Consent (Consent) Form" was obtained from the parents of the athletes who wanted to participate in the study voluntarily. The study was prepared in accordance with the principles of the Declaration of Helsinki. Body weights, heights and blood parameters were taken for pre-test and post-test measurements in both groups. Appropriate SPSS statistical program was used in the analysis of the obtained data. The Shapiro-Wilk test was used to determine whether the data showed a normal distribution. Intragroup “Paired t test” to determine whether there is a difference before and after training; The difference between the groups was analyzed using the "Independent-t test". The significance level was evaluated according to the 0.05 significance level. Result: According to the in-group analysis comparison, while there was a significant difference in all pre- and post-test measurements of the experimental group, there was no difference in the control group. According to the comparison of the between-group analysis of the experimental and control groups, a statistically significant diffrence was found in the lactic acid pre-post test and iron pre test measurements, there was no significant diffrence in other measurements. Conclusion: As a result, it has been determined that 8-week functional training and narrow field studies applied to U14-U15 football players have effects on some selected blood parameters.